PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE (RTE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON KELAS X DI SMAN 1 TEMPULING-INDRAGIRI HILIR - Desfarita Desfarita; R. Usman Rery; Miharty Miharty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe research about application of cooperative learning model rotating trio exchange (RTE) has been done to know effect of cooperative learning model rotating trio exchange of student’s achievement at hydrocarbon subject in class X SMAN 1 Tempuling-Indragiri Hilir and to determine effect of cooperative learning model rotating trio exchange of student’s achievement at hydrocarbon subject in class X SMAN 1 Tempuling-Indragiri Hilir. The research is form of experimental research with pretest-posttest design. Samples consist of two classes; class X1 as a class experiment and class X2 as a class control of randomly chosen after the normality test and homogeneity test. Experimental is a class that is treated by applying model rotating trio exchange. Can improve student’s achievement on hydrocarbon subject in class X SMAN 1 Tempuling-Indragiri Hilir in crease student’s achievement with effect 5,507%.Keywords : Cooperative Learning Model, Rotating Trio Exchange (RTE), Student’s Achievement,Hydrocarbon.